2012
DOI: 10.1016/j.socscimed.2011.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Disability and dignity-enabling home environments

Abstract: In Canada where long-term care is primarily oriented to elderly persons and affordable accessible housing is limited, younger disabled adults may be living in circumstances that do not meet their health needs and contribute to their social exclusion. The purpose of this study was to undertake an ethical analysis of what constitute an 'adequate' home environment for adults with significant mobility disabilities. An integrated design was used that combined qualitative interviews with normative ethical analysis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
0
28
0
1
Order By: Relevance
“…Empirical research and policy reform point to the inadequacy of adult-oriented long-term care homes for younger adults, and have grounded calls for increased services to allow children to live in family homes and/or family-friendly group home settings [15,21,23,24]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research and policy reform point to the inadequacy of adult-oriented long-term care homes for younger adults, and have grounded calls for increased services to allow children to live in family homes and/or family-friendly group home settings [15,21,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…In previous work we have suggested that, at a minimum, all homes should promote individual dignity beyond the provision of safety and basic care [23]. Furthermore, Asch and colleagues [49] posit that institutional homes should be designed to enable continuity of services across the lifespan as residents’ care needs change over time.…”
Section: Discussionmentioning
confidence: 99%
“…Feminist ethics focus on the interdependent, unequal, and emotionally charged relationships that shape human lives and interactions (Brennan, ). Critical narrative approaches incorporate ordinary lived experience and seek to understand the social, cultural, and institutional narratives within which individual experiences are constituted, shaped, expressed, and enacted (Gibson et al, ; Peter, ). Walker's () expressive‐collaborative model of morality, in which moral and social worlds are intertwined, allows for structures of power within relationships and institutions to be made visible and facilitates an exploration of who controls moral decision making as well as the effect that control has on more vulnerable persons.…”
Section: Methodsmentioning
confidence: 99%
“…Although empirical research in this area is growing, there is limited knowledge surrounding the barriers and facilitators to mobility and social participation that are encountered in the neighborhood physical environment by MAT users (Botticello, Rohrbach, and Cobbold 2015;Clarke 2014;Harris, Yang, and Sanford 2015). Understanding the opportunities and constraints afforded by the neighborhood physical environment is central to understanding the mobility and social participation of this population, and could inform interventions and policies to foster independence, health, and well-being of MAT users, as well as contribute to the emergent literature about enabling environments (O'Brien 2014; Gibson et al 2012;Duff 2009;Hansji, Wilson, and Cordier 2015).…”
Section: Points Of Interestmentioning
confidence: 99%